Design and Evaluation of a Structural Reinforced Small Intestinal Submucosa Vascular Graft for Hemodialysis Access in a Porcine Model. Issue 2 (March 2018) - Jaramillo, Juliana; Valencia-Rivero, Karen T.; Cedano-Serrano, Francisco J.; López, Rocío; Sandoval, Néstor; Briceño, Juan C.
Abstract : Synthetic vascular access for hemodialysis exhibits biological and mechanical material properties mismatch with the native vessels. These limitations prevent infiltration of endothelial cells and decrease grafts long-term patency, particularly in small diameter vessels. We aimed to design a curved structural reinforced small intestinal submucosa (SIS) vascular graft for hemodialysis access and to evaluate in a porcine animal model graft patency by Doppler ultrasonography, tissue remodeling by histology, and vascular wall Young's modulus after implantation by biaxial tensile test. Curved 4 mm inner diameter, 0.5 mm thickness, and 150 mm length SIS grafts were designed. Small intestinal submucosa vascular grafts were preliminary tested in vivo in a porcine animal model (n=3) constructing an arteriovenous fistula between the carotid artery and the jugular vein; GORE-TEX grafts were implanted as control. Small intestinal submucosa grafts remained patent 46 ± 7 days against the control, 30 ± 3 days. Histology showed thrombus formation on the lumen (80% to 100% surface area) of all explanted grafts. Small intestinal submucosa grafts exhibited neovascularization and endothelial cells alignment on the graft wall, indicating regeneration. Biaxial tensile tests demonstrated no significant differences in Young's moduli between SIS grafts ( E Circ = 2.5 ± 1.0 MPa, E Long = 5.7 ± 2.6 MPa) and native artery ( E Circ = 1.4 ± 0.8 MPa, E Long = 5.5 ± 1.1 MPa), indicating similar wall stiffness. This study proposes an innovative design of a tissue-engineered vascular graft for hemodialysis access that, besides its structural characteristics similar to those of current synthetic grafts, could enhance biological performance because of its composition.